Diagnosis and treatment of HS after endoscopic thyroid surgery: case report and brief literature review - Deng, Yuqing; Ding, Guoqian (Frontiers in Surgery, 2023)
Background: Horner syndrome (HS) is a rare condition due to damage to the 3neuron sympathetic pathway anywhere between the posterior-lateral nuclei of the hypothalamus and the oculosympathetic fiber, particularly as a post-thyroidectomy symptom. In this case report, we present a case of HS following endoscopic thyroid surgery (ETS) and briefly review the literature. Case report: During a routine physical examination, a 29-year-old female patient was incidentally found to have multiple nodules in the right thyroid. She was subsequently admitted to the Department of General Surgery for further examinations and treatment. A fine-needle aspiration biopsy confirmed malignancy in these nodules. As a result, the patient underwent radical resection of the right thyroid and ipsilateral central lymph node dissection using endoscopy. Pathological diagnosis revealed papillary thyroid carcinoma. Unexpectedly, on the third day after the operation, the patient was diagnosed with Horner syndrome based on the presence of miosis and ptosis. After one week of follow-up, the symptoms related to HS significantly improved. Conclusion: Horner syndrome is an uncommon complication of thyroidectomy in patients undergoing ETS. Therefore, it is crucial to perform careful operations and minimize iatrogenic surgical damage to reduce the incidence of HS. This case serves as a reminder that making rational judgments and implementing appropriate measures are essential for achieving a favorable prognosis and preserving facial aesthetics.